Synthesis and area-wide validation of IPM technology and its economic analysis for eggplant (Solanum melongena) - HALDER, JAYDEEP; SARDANA, H R; PANDEY, MANOJ KUMAR; MEENA, B R; BHAT, M N (The Indian Journal of Agricultural Sciences, 2022)
Field experiments were conducted during 2019–21 in Varanasi, Mirzapur and Bhadohi districts of Uttar Pradesh, with a view to study validation and economic viability of IPM technology in eggplant (Solanum melongena L.) in a farmers’ driven approach. The synthesized improved IPM technology comprising seed treatment with Trichoderma viride @5 g/kg seed; seedling root dip in carbendazim 50 wp @1 g/l followed by chlorantraniliprole 18.5 sc @0.5 ml/l solution against seed borne diseases and shoot and fruit borer, respectively, clipping of borer damaged shoots at weekly interval, installation of pheromone traps @25–30 traps/ha for mass trapping of brinjal shoot and fruit borer (BSFB), need based spray (ETL>5%) of chlorantraniliprole 18.5 sc @0.35 ml/l or emamectin benzoate 5 SG @0.4 g/l or fenpropathrin 30 ec @0.33 ml/l against BSFB, installation of yellow sticky traps, application of Azadirachtin 0.03% @5 ml/l and need based spray of thiamethoxam 25 wg @0.4 g/l or fenpropathrin 30 ec @0.33 ml/l against sucking pests like whiteflies and hoppers, collection and destruction of borer and Phomopsis blight infected fruits, Sclerotinia white rot infected twigs and branches and little leaf affected plants periodically, need based application of carbendazim 50 wp @0.5 g/l for management of Phomopsis blight and white rot, were found effective in reducing the incidence of pests and minimizing the yield losses. The adoption of IPM technology also resulted in reducing the number of chemical sprays to 10 from 21–24 in farmers’ practices (FP) fields in a season with higher fruit yields of 51.1 and 45.3 t/ha in IPM, 39.6 and 33.7 t/ha in FP and 25.7 and 20.4 t/ha in untreated control fields with higher incremental benefit cost (B:C) ratio of 4.61:1 and 4.86:1 in IPM than 3.16:1, 3.24:1 in non-IPM and 2.53:1, 2.42:1 in untreated control plots during 2019–20 and 2020–21, respectively.